2016
DOI: 10.1093/mnras/stw2810
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive long-term study of the radio and X-ray variability of NGC 4051 Paper II

Abstract: The origin of the low luminosity radio emission in radio-quiet AGN, is unknown. The detection of a positive correlation between the radio and X-ray emission would imply a jet-like origin, similar to that seen in 'hard state' X-ray binary systems. In our previous work, we found no believable radio variability in the well known X-ray bright Seyfert 1 galaxy NGC 4051, despite large amplitude X-ray variability. In this study we have carefully re-analysed radio and X-ray observations using the same methods as our p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…RQ AGN have shown cm/mm-band variability on daymonth-year timescales (e.g., Wrobel 2000; Chatterjee et al 2009;Mundell et al 2009;Baldi et al 2015), which, at face value, appears to be similar to the behaviour of binaries in their hard states. Nevertheless, simultaneous radio/X-ray monitorings are rare and have so far yielded only weak or no correlations, with ambiguous results (see Figure 6, Bell et al 2011;King et al 2011King et al , 2013Jones et al 2011Jones et al , 2017.…”
Section: Comparison With Other Accreting Sourcesmentioning
confidence: 99%
“…RQ AGN have shown cm/mm-band variability on daymonth-year timescales (e.g., Wrobel 2000; Chatterjee et al 2009;Mundell et al 2009;Baldi et al 2015), which, at face value, appears to be similar to the behaviour of binaries in their hard states. Nevertheless, simultaneous radio/X-ray monitorings are rare and have so far yielded only weak or no correlations, with ambiguous results (see Figure 6, Bell et al 2011;King et al 2011King et al , 2013Jones et al 2011Jones et al , 2017.…”
Section: Comparison With Other Accreting Sourcesmentioning
confidence: 99%
“…However, in order to truly test the connection between the mm-wave and X-ray sources of RQ AGN, simultaneous monitoring is essential. Diligent attempts at 5 and 8.5 GHz, either focus on more RL objects (Bell et al 2011), or meet limited success in RQ ones (Jones et al 2017). No such campaign, as far as we know, exists for higher frequencies.…”
Section: Connection To X-raysmentioning
confidence: 99%
“…They argue that in most cases the jet loses most of its power within the innermost kiloparsec. Jones et al (2017) study the radio variability of J1203+4431 but find no significant signs of it. They hypothesise that the jet-like structure results from an earlier period of higher activity, and that at the moment the source is at a low-activity state.…”
Section: J1203+4431mentioning
confidence: 93%
“…Very high-resolution observations with the VLBA at 1.7 GHz (Doi et al 2013) and with the JVN at 22 GHz (Doi et al 2015) do not detect the source. Several studies have suggested that the origin of the inner structure is the AGN activity (e.g., Gallimore et al 2006;Maitra et al 2011;Jones et al 2017). Based on broadband SED modelling Maitra et al (2011) conclude that the source hosts a mildly relativistic jet/outflow.…”
Section: J1203+4431mentioning
confidence: 99%